Biotechnological Approaches for Host Plant Resistance to Insect Pests - Kumari, Pritam; Jasrotia, Poonam; Kumar, Deepak; Kashyap, Prem Lal; Kumar, Satish; Mishra, Chandra Nath; Kumar, Sudheer; Singh, Gyanendra Pratap (Frontiers in Genetics, 2022)
Annually, the cost of insect pest control in agriculture crosses billions of dollars around the world. Until recently, broad-spectrum synthetic pesticides were considered as the most effective means of pest control in agriculture. However, over the years, the overreliance on pesticides has caused adverse effects on beneficial insects, human health and the environment, and has led to the development of pesticide resistant insects. There is a critical need for the development of alternative pest management strategies aiming for minimum use of pesticides and conservation of natural enemies for maintaining the ecological balance of the environment. Host plant resistance plays a vital role in integrated pest management but the development of insect-resistant varieties through conventional ways of host plant resistance takes time, and is challenging as it involves many quantitative traits positioned at various loci. Biotechnological approaches such as gene editing, gene transformation, marker-assisted selection etc. in this direction have recently opened up a new era of insect control options. These could contribute towards about exploring a much wider array of novel insecticidal genes that would otherwise be beyond the scope of conventional breeding. Biotechnological interventions can alter the gene expression level and pattern as well as the development of transgenic varieties with insecticidal genes and can improve pest management by providing access to novel molecules. This review will discuss the emerging biotechnological tools available to develop insect-resistant engineered crop genotypes with a better ability to resist the attack of insect pests.